Exploring adaptive e-learning of architectural education using i-Ta’leem platform - Abdullah, Fadzidah (2017)
This research aims to explore the potential of having architectural education disseminated using adaptive e-learning platform of i-Ta’leEM (An innovative online teaching and learning system). i-Ta’leEM is developed in IIUM to provide innovative teaching and learning environmental systems, but the effectiveness and appropriateness of architectural education to adapt with this and any other e-learning mechanisms has not been empirically analyzed. The objectives of the research are: to examine the effectiveness of i-Ta’leEM as the platform of knowledge dissemination in architectural education; and to analyze the potential of using i-Ta’leEM in monitoring the development of students’ architectural design skill. This research takes the approach of action research, where researchers will personally involve in the experience of testing the potential and effectiveness of using i-Ta’leEM as platform for e-learning in architectural education. Both quantitative and qualitative approaches are utilized in conducting the research. This research has the proposition that dissemination of knowledge and development of skills in architectural education could be effectively accomplished via e-learning mechanism. This research would provide guidance on how architectural education would best adapt e-learning platform, and perhaps establish comprehensive module of utilizing e-learning in architectural education.